2020
DOI: 10.1111/jonm.13079
|View full text |Cite
|
Sign up to set email alerts
|

Organisational and professional turnover intention among nurse managers: A cross‐sectional study

Abstract: Aim We sought to examine factors associated with organisational and professional turnover intention among nurse managers. Background Turnover among nurse managers is an ongoing problem in many health care institutions worldwide. While many studies exist that have examined factors contributing to organisational turnover intention, surprisingly, little is known about which factors contribute to nurse managers' decisions to quit the profession. Methods This cross‐sectional study involved 240 nurse managers workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 52 publications
2
71
1
Order By: Relevance
“…Intent to leave the facility was assessed using this item, “I am thinking about leaving this healthcare facility,” while intent to quit from the nursing profession was examined by this item, “I am thinking about leaving nursing as a profession.” Nurses indicated their responses on each item of the scale using a Likert scale which ranged from 1 [strongly disagree] to 5 [strongly agree]. In this study, the value for the test–retest reliability of the two items was .92 and .91, respectively, higher than in the previous study (Labrague, 2020).…”
Section: Methodscontrasting
confidence: 49%
“…Intent to leave the facility was assessed using this item, “I am thinking about leaving this healthcare facility,” while intent to quit from the nursing profession was examined by this item, “I am thinking about leaving nursing as a profession.” Nurses indicated their responses on each item of the scale using a Likert scale which ranged from 1 [strongly disagree] to 5 [strongly agree]. In this study, the value for the test–retest reliability of the two items was .92 and .91, respectively, higher than in the previous study (Labrague, 2020).…”
Section: Methodscontrasting
confidence: 49%
“…(2011) concluded that transformational leadership provides an improvement in the performance of nurses' functions, increasing levels of self‐efficacy and work engagement. Labrague (2020) identified job satisfaction, stress and work–family conflict as significant predictors of organizational and professional turnover intent in managing nurses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite all the efforts, research in different contexts and countries has shown that work contexts are far beyond healthy work environments (Labrague, 2020) and are recognized as a source of suffering (Areosa, 2018). Considering the importance of factors that enhance workers’ well‐being, recent research focused on areas such as workaholism, engagement and family interaction (Clark, Smith, & Haynes, 2020; Di Stefano & Gaudiino, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, researchers looked at turnover intent rather than looking at actual turnover [14]. Previous research has shown that an employee's intent to leave an organization is consistently correlated with actual turnover [14,20]. As a result, measuring turnover intention is more valuable than taking corrective action after actual turnover [2].…”
Section: Intention To Turnovermentioning
confidence: 99%
“…As a result, organizations should make every effort to keep their employees as long as possible. Furthermore, measuring Turnover Intention is more valuable than taking corrective action following actual turnover occurred [20].…”
Section: Implications For Managersmentioning
confidence: 99%